Alert today-alive tomorrow: A report of unusual traffic deaths involving bamboo - Keisham, Supriya; Phanjoubam, Memchoubi; Seram , Elizabeth (Journal of Indian Academy of Forensic Medicine, 2019)
Road traffic injuries are currently estimated to be the ninth leading cause of death across all age groups globally, and are predicted to  become the seventh leading cause of death by 2030. This rise is driven by the escalating death toll on roads in low and middle income  countries, particularly in emerging economies where urbanization and motorization accompany rapid economic growth. Two cases of  unusual traffic deaths involving bamboo are reported in this paper. On separate instances, the victims were coming on two wheelers  and collided with another vehicle carrying bamboo poles. In both instances, the victims died from injuries inflicted by the bamboo  poles. “Being alert today will keep one alive tomorrow” is the message suggested by this paper.
Keywords: Road traffic accident; Fatal injury; Bamboo; Laceration of heart; Maxillary artery laceration